Increasing learning outcomes for volleyball passing using cooperative learning methods - Endang Pratiwi; Andi Kasanrawali; Norma Anggara (Sriwijaya Journal of Sport, 2023)
This study aims to determine the learning outcome passing volleyball at SMK Bhakti Nations Banjarbaru South Kalimantan using cooperative learning methods. The research used is PTK which uses 2 cycles and there is a design for each cycle, plans, observations, actions, or results and finally reflection or evaluation. The target in this study were students of SMK Bhakti Nations Light Vehicle Engineering class, as many as 24 students. Sources of data obtained through the initial test and final test passing under volleyball. Data analysis techniques used in this research is descriptive. The results showed that through a cooperative approach from initial tests through to the final test. The average result of the skill of the initial test was 575 and the average value of 23.95, only 30.26% with cooperative learning approach will be unchanged or increased value overall to be 980 with the average value per individual 40.83, or 51.57% in Cycle I. Later, the second cycle increased to 70.33%, or more than 70%, or more than half of the sample has been said to be used to make passing under volleyball properly Conclusions from this research is the method of group learning positive effect in improving student achievement, which is characterized by increase the thoroughness.